The Insensitivity to Mathematics and Suggested Solution - Usluoğlu, Büşra; Toptaş, Veli; Özdemir, Bennur (Elementaria: Journal of Educational Research, 2024)
Mathematics is an important science that shapes the future as it did in the past. The mathematical knowledge, which helps explain other sciences, needs to be transferred and adopted to the next generation with this awareness. However, nowadays, mathematics is increasingly presented as a subject that should be avoided and is famous for its failures. The feeling of insensitivity towards mathematics brought about by mathematical anxiety and fear is now one of the important issues that needs to be solved on its own. For this purpose, in addition to increasing students' interest and sensitivity towards mathematics, teachers and parents must support this motivation in a necessary and sufficient way. In this study, it is discussed what the insensitivity and anxiety that develops towards mathematics are and under what conditions they are triggered. In addition, solution suggestions for eliminating mathematical insensitivity were presented in line with the opinions of students, teachers and parents, with whom semi-structured interviews were conducted in accordance with the purpose and scope of the study. The data of the study was analyzed by content analysis and the results were added to the solution suggestions headings in the study.